Redes e sistemas do tráfico de drogas no Rio de Janeiro: uma tentativa de modelagem - Souza, Marcelo Lopes de (Anuário do Instituto de Geociências, 1996)
Undoubtedly, most of the drug trade for local consumption in Rio de Janeiro is organized by quadrilhos (gangs) based in fovelas (shanty-towns), which are linked to different criminal organizations or networks (comandos). The most important criminal network of Rio de Janeiro, the Comando Vermelho (Red Commando) was created in the late 1970s. However, the mass media tend to give a false image of drug traffic and its structure. Although newspapers and television paaa the idea that the leaders of the drug traffic in the favelas are very powerful, they are to a considerable extent only the underlings of the drug trade's real sponsors, who have connection with important politicians, businessmen etc.; the most important traffickers, who operate at the level of the import/export/wholesale trade system, do not live in shanty-towns. Furthermore, the criminal organizations, which operate in the context of local retail trade (retail trade system), are not very centralized: the Comando Vermelho itself, whose founders are dead or in jail, is today essential)' a unstable solidarity network among inmates.